Effectiveness Ethanol Extract of Tinospora crispa L, Cymbopogon citratus, Alpinia purpurata K Schum, and Alpinia galanga L in Lowering Mouse Cholesterol Levels - Khoirul Ngibad; Dane Prastio; Evinia Eka Novem; Ragil Tri Sutrisno; Agustina Wulandari; Gaby Ayu Patricia; Cicik Wijayanti (Justek : Jurnal Sains dan Teknologi, 2026)
Hypercholesterolemia is a lipid metabolism disorder that increases the risk of cardiovascular disease. Although statins are effective, long-term use may cause side effects, prompting the exploration of natural alternatives that contain bioactive flavonoids, phenolics, and terpenoids with hypocholesterolemic activity. This study aimed to evaluate the cholesterol-lowering effects of ethanol extracts of Brotowali (Tinospora crispa L.), Lemongrass Stem (Cymbopogon citratus), Red Galangal (Alpinia purpurata K. Schum.), and White Galangal (Alpinia galanga L.) in hypercholesterolemia-induced male mice. A true experimental study was conducted using 36 male mice divided into six groups: Negative Control (I), Positive Control (II), Drug Control (Simvastatin) (III), and three extract groups (IV–VI) receiving doses of 14, 28, and 56 mg/20 g BW. After a seven-day adaptation period, the animals were administered propylthiouracil for 14 days to induce hypercholesterolemia, which was confirmed by blood cholesterol measurement on Day 15. Subsequently, simvastatin or the extracts were administered for three days, and cholesterol levels were measured on Day 18 using a spectrophotometric method. The results showed that all extracts reduced cholesterol levels compared to the Positive Control (194.65 ± 8.26 mg/dL), but were less effective than simvastatin (103.15 ± 15.54 mg/dL). Brotowali reduced levels to 140.90 ± 10.10 mg/dL; Lemongrass Stem to 143.47 ± 21.65 mg/dL. Red Galangal reached 138.79 ± 10.69 mg/dL and White Galangal 139.03 ± 16.53 mg/dL at the highest dose (56 mg/20 g BW). In conclusion, the four ethanol extracts showed potential as natural antihypercholesterolemic agents, with Red and White Galangal demonstrating the greatest cholesterol-lowering effects at a dose of 56 mg/20 g BW, although their efficacy remained lower than simvastatin.